HAK RESTITUSI BAGI ANAK YANG MENJADI KORBAN TINDAK PIDANA KEKERASAN SEKSUAL - Benget Hasudungan Simatupang; Clarita William; Sudirman Sitepu; Pipi Susanti (University Of Bengkulu Law Journal, 2023)
Restitution arrangements are still lacking in terms of fulfilling the rights of victims of criminal acts. It is necessary to study the application for the right of restitution given to children as victims of criminal acts of violence and the legal consequences of restitution not being paid by the perpetrators. This study uses a type of normative research. The collection of legal materials was carried out using literature study techniques and analyzed using descriptive analysis. Government Regulation Number 43 of 2017 does not regulate coercion if the perpetrator is unable to carry out restitution, so there is no guarantee that restitution can be paid to a child as a victim of a crime. Therefore, this causes no certainty for children who are victims of criminal acts to receive restitution and imposition of sanctions against perpetrators of criminal acts who do not pay restitution in accordance with court decisions that have permanent legal force. Restitution in Law Number 12 of 2022 concerning Crimes of Sexual Violence emphasizes that in the event that the confiscated assets of the convict are not sufficient to pay restitution, the convict will be subject to a replacement prison sentence which does not exceed the threat of the principal sentence. The state then provides victim compensation.